Carbonyl Cyanide m-Chlorophenylhydrazine (CCCP) Reverses Resistance to Colistin, but Not to Carbapenems and Tigecycline in Multidrug-Resistant Enterobacteriaceae - Osei Sekyere, John; Amoako, Daniel G. (Frontiers in Microbiology, 2017)
Background: Carbapenems (CAR), colistin (CST), and tigecycline (TGC) alone or in combination therapy has become the last-resort antibiotics for treating infections caused by multidrug resistant (MDR) bacteria. However, resistance to these reserve antibiotics are increasingly being reported worldwide. Hence, the quest to find other agents that will synergistically restore the efficacy of these antibiotics have increased. Methods: Sixty-three clinical Enterobacteriaceae isolates comprising of Klebsiella pneumoniae (n = 24), Enterobacter spp. (n = 15), Serratia marcescens (n = 12), Citrobacter freundii (n = 8), Escherichia coli (n = 2), and K. oxytoca/michiganensis (n = 2) with known carbapenem resistance mechanisms and undescribed CST and TGC resistance mechanisms were subjected to broth microdilution and meropenem (MEM) disc synergy test in the presence and absence of carbonyl cyanide m-chlorophenylhydrazine (CCCP), a H+ conductor (protonophore). Results and conclusions: Susceptibility to MEM, imipenem (IMP), CST, and TGC was found in only 2, 0, 17, and 9 isolates respectively. Addition of CCCP reversed resistance to CST, TGC, IMP, and MEM in 44, 3, 0, and 0 isolates respectively; CST had the highest mean minimum inhibitory concentration (MIC) fold change (193.12; p < 0.0001) post CCCP compared to that of MEM (1.70), IMP (1.49) and TGC (1.16). Eight isolates tested positive for the MEM-CCCP disc synergy test. We concluded that CCCP reverse CST resistance in CST-resistant Enterobacteriaceae. Although CCCP is an experimental agent with no therapeutic value clinically, further studies are necessary to decipher the mechanisms underlying the CST-CCCP synergy to inform the development of adjuvants that could be therapeutically effective in CST-resistant infections.